Analisis Bibliometrika Artikel pada Jurnal Info Bibliotheca Universitas Negeri Padang Tahun 2022 - 2024 - Rahma Intan Oktiara; Gustina Erlianti (Jurnal Penelitian Teknologi Informasi dan Sains, 2025)
This study aims to describe the half-life and obsolescence level of literature used in the Info Bibliotheca Journal articles of Padang State University in 2022-2024. This study was conducted using a quantitative method with a descriptive approach. The entire population was sampled in this study, with a total sample of 48 articles. Data were collected, analyzed using the half-life and obsolescence formulas, and conclusions were drawn. The results showed that the expired citations were 411 citations (50.24%) and the most recent were 407 citations (49.67%). The expiration rate of literature in the Info Bibliotheca Journal articles of Padang State University is 7 years.